THE INTENSIFICATION OF THE ULTRAFILTRATION PROCESSOF A MIXTURE OF WHEY WITH JERUSALEM ARTICHOKE JUICE - Sergey Petrovich Babenyshev; Dmitry Sergeevich Mamay; Petr Vasilievich Rozhkov; Viktor Pavlovich Utkin; Nikolay Andreevich Shapakov (Современная наука и инновации, 2022)
Low efficiency of ultrafiltration of liquid polydisperse systems has identified experimental and theoretical research for the development and justification of the methodology ofprocess intensification.